PERSEPSI DAN PERILAKU REMAJA PUTRI TENTANG PEMBALUT YANG DIPERGUNAKAN DALAM KEHIDUPAN SEHARI-HARI - Dewi, Komang Ayu Purnama; Nurtini, Ni Made; Mastryagung, Gusti Ayu Dwina (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2017)
Introduction: Nowadays, pads almost become a staple for women. Evidently, from about 118 million women in Indonesia, 67 million are women of childbearing (still menstruation and the pads), then estimated at no less than 1.4 billion pads / per month, which is used by women in Indonesia (Anonymous, 2015). Developing information relating to dangerous bandage issued olek YLKI has been denied by the minister of health stating that the pads are used still within safe levels it is contrary to the regulations made by the Ministry of Health, the Minister Regulation No. 472 of 1996 regarding security and supervision of hazardous materials, one of which is chlorine. This study aims to determine the Perceptions and Behavior of Young Women of dressings used in everyday life.Methodology: The method of research is descriptive with cross sectional approach, with a sample size is 490 female students from all over Bali STIKES taken by accidental sampling in accordance with the inclusion and exclusion criteria.Results: The majority of girls are 256 people (52.2%) had a negative perception of the pads that are used in everyday life. The majority of girls are 290 people (59.2%) had a bad behavior on pads that are used in everyday life.Discussion: Most young women have negative perceptions about the pads that are used in everyday life. Most young women have good behavior on pads that are used in everyday life.Keywords: perception, behavior, young women, pads